MICROPROPAGATION OF Gypsophila paniculata THROUGH CULTURE OF NODAL SEGMENTS - QUOIRIN, Marguerite Germaine Ghislaine; BIASI, Luiz Antonio; RIOS, José Fernando; CUQUEL, Francine Lorena (Scientia Agraria, 2008)
Gypsophila paniculata is one of the principal cut flowers on the Brazilian market. Commercially it is propagated by in vitro methods, however very few scientific information is available about it. The goal of this work was to establish in vitro technology to propagate Gypsophila paniculata through nodal segments. Gypsophila plants cultivar Golan obtained from a grower were used to start this research. They were planted in pots and maintained inside greenhouse under controlled temperature and relative humidity. Nodal segments one to two centimeters long were removed from these plants and immersed in alcohol 70% during 30 s, followed by sodium hypochlorite 2% during 10 min. They were then cultured in vitro on MS medium containing two concentrations of kinetin (KIN), with or without 3 mM naphtalenacetic acid and with 0.3 mM gibberellin (GA3). Better multiplication of the nodal segments was obtained in MS media containing 0.5 mM KIN and 0.3 mM GA3.